Dualism in E-Commerce Dispute Resolution: Between Litigation and Arbitration - Setyawan, Vincentius Patria (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2024)
The purpose of this research is to analyze the Legal Challenges in E-commerce Dispute Resolution: Arbitration and Litigation Approaches. This type of research is a literature review, with data collection through documentation. Data analysis is conducted using SLR (Systematic Literature Review). The research findings indicate that the legal challenges in resolving e-commerce disputes involve regulatory complexities that are rapidly evolving amidst the dynamics of online transactions. Arbitration and litigation approaches are the two primary options that parties involved in e-commerce disputes must consider. Arbitration offers speed and confidentiality, while litigation provides a more structured process with public disclosure of information. However, the biggest challenge remains the adaptation of the existing legal system to the dynamics of technological advancements and the continuously growing e-commerce business.